Primary peritoneal carcinoma with late-phase pulmonary metastases: a case report - Naoki Ozeki; Shuhei Hakiri; Hisashi Tateyama; Kohei Yokoi; Toyofumi Chen-Yoshikawa (Surgical Case Reports, 2019)
Abstract Background Primary peritoneal carcinoma (PPC) is a very rare and aggressive type of malignancy with a poor prognosis. Case presentation A 66-year-old woman was referred to our hospital with two pulmonary nodules that developed after PPC resection and postoperative adjuvant chemotherapy administered 5 years earlier. Computed tomography revealed a 1.3-cm-sized nodule in the left lung with a small airspace in the posterior basal segment and a 0.9-cm-sized solid nodule in the apico-posterior segment that grew slightly within a 2-month period. 18F-Fluorodeoxyglucose-positron emission tomography of these lesions revealed respective maximum standardized uptake values of 7.11 and 2.46. Her serum cancer antigen-125 level remained within the normal range, despite elevation before the first surgery. The posterior basal segment and superior division were subjected to anatomical segmentectomy. An intraoperative frozen section examination could not distinguish metastatic PPC from primary lung cancer. Immunopathologically, the two nodules were identified as metastatic PPC. Conclusions Our findings suggest that PPC patients may develop late-phase thoracic recurrence that is difficult to diagnose clinically after initial treatment in a potentially resectable setting.